Wireless monitoring system (Smart home – Security systems) - Noorashidin, Abdul Rahim (Universiti Malaysia Perlis, 2009)
Wireless monitoring system is a project which could give assurance for user to protect their homes from burglars, thieves and criminals. This idea was acquired after intensive observation based on local news nowadays which reveals crime case due to recklessness and carelessness of the residence. In addition to that, cable security system is in high risk to malfunction due to damage or disconnected wire. Wireless monitoring system give us unlimited transmission data compared to cable and it uses air (radio frequency) as a medium to transmit data. It works fast, accurate and users will not worry about disconnected wire anymore. The system is designed into two modes which are ‘home mode’ and ‘away mode’. Only selected sensors are functional when home mode is activated. If away mode is activated, it gives fully monitoring for user’s house. MPLAB Integrate Development Environment (IDE) v7.00 software has been adopted in this project and C language is selected for programming methods. This project has been divided into two main phases; software development and hardware development. In the software development, it is involved with the design entry, simulation process and downloads process. Meanwhile, the hardware development covers sensor circuit, transmitter circuit and receiver circuit construction. Based on the result obtained, the system has function properly when the sensor triggered, transmitter sent the data, receiver received the data and the buzzer and lamp indicator will be activated.